Gel Formulation of Lipid Nanoparticles and Zn Nanoparticles of Okra Fruit Extract (Abelmoschus Esculentus L.) and Sunscreen Activity Test - Astutiningsih, Christina; Ebta Narasukma Anggraeni (PT Inovasi Pratama Internasional, 2022)
Depletion of the ozone layer and environmental pollution has a negative impact on the skin because these conditions make it easier for UV rays to damage and even cause skin cancer. One of the efforts made to reduce the harmful effects of UV rays can be overcome with quality cosmetic products using nanotechnology. This study aims to formulate a lipid nanoparticle gel with okra fruit extract as the active substance and the Zn nanoparticle gel with okra fruit extract as bioreduction. Lipid nanoparticles were prepared from lecithin phospholipids and okra fruit extract by heating at 600°C and sonification for 30 minutes. Meanwhile, Zn nanoparticles were prepared by adding Zn acetate extract to okra fruit extract in a ratio of 1:9 and heating for 90 minutes. Zn nanoparticles of fruit extracts have a wavelength of 360-380. The average particle size of lipids was 140.734 ± 4.53nm, while the average particle size of Zn nanoparticles was 136.79 ± 6.41nm. The physical characteristics of the gel from lipid nanoparticles are as follows: viscosity of 4225 pcs; pH 7.53; spreadability of 4.54 cm and adhesion of 5.65 seconds while the viscosity of the Zn nanoparticle gel was 4123 pcs; pH 7.24; spreading the power of 4.11 cm and adhesion power of 5.42 seconds. Lipid nanoparticle gel preparation of okra fruit extract has an SPF value of 20.1076, erythema is 0.2172% and percent pigmentation is 0.2295%, while Zn nanoparticle gel has an SPF value of 21.7865, erythema is 0.2173% and percent pigmentation is 0,2105%.